The Taiji Model of Self - Wang, Feng-Yan; Wang, Zhen-Dong; Wang, Rou-Jia (Frontiers in Psychology, 2019)
An important theme in the development of self psychology is the attempt by scholars to construct a self-model with universal cultural adaptability. Among them, representatives are the tripartite model of self built by Triandis, the theory of the independent self and interdependent self proposed by Markus & Kitayama, Yang Kuo-Shu’s four-part theory of the Chinese self, Hwang Kwang-Kwo’s Mandala model of self, and Shiah Yung-Jong’s Nonself Theory. However, these models have a difficult time explaining the structure and development of the Chinese self in Chinese cultural background. After pondering over Chinese traditional culture and the Chinese self, inspired by the archetype of Taiji diagram, in this paper, we construct the Taiji Model of Self. The Taiji Model of Self can not only properly represent the Chinese self-structure, but also explain the growth course of the Chinese self and four kinds of life realms of Chinese people with satisfactory cultural and ecological validity.